Medicinal uses, phytochemistry, and pharmacological properties of Piper aduncum L. = Kegunaan perubatan, fitokimia dan sifat farmakologi piper aduncum L. - Bakhtiar, M. Taher; Amri, Mohamad Shahreen; Darnis, Deny Susanti; Abdul Kudos, Muhammad Badri; Md Nor, Nur Fasya Ajda; Syukri, Yandi (Penerbit Universiti Kebangsaan Malaysia, 2020)
Piper aduncum L., commonly known as ‘spiked pepper’, has various uses in traditional medicine that include treating wounds, skin boils, infections, and diarrhoea. Its properties as an anti-parasitic, antimicrobial, insecticidal, antitumor, and anticancer agent indicates that it could have further therapeutic potential in treating infections and cancers. The aim of this review was to provide a comprehensive summary of the traditional uses, phytochemistry and pharmacological properties of P. aduncum. Data were collected from electronic databases from 1978 to 2019. The plant is traditionally used for treating diarrhoea in Peru and for its wound-healing properties in Brazil and Papua New Guinea. Phenolics, monoterpenes, sesquiterpenes, and chromene have been found in the P. aduncum plant, and these bioactive compounds contribute to its anti-parasitic, antimicrobial, insecticidal, antitumor, and anticancer properties. Several pharmacological activities of P. aduncum have been reported, most notably in the treatment of infectious diseases and cancer. However, information regarding its safety and efficacy in humans is lacking. Further study is needed to examine the benefits of P. aduncum and its potential applications in a clinical setting. ************************************************************************** Piper aduncum L., yang dikenali sebagai lada berduri, mempunyai pelbagai kegunaan dalam ubat tradisi termasuk merawat luka, bisul kulit, jangkitan dan cirit-birit. Sifatnya sebagai agen anti-parasit, antimikrob, insektisid, antitumor dan antikanser menunjukkan bahawa ia mempunyai potensi terapeutik dalam merawat jangkitan dan kanser. Tujuan kajian ini adalah untuk memberikan ringkasan komprehensif mengenai kegunaan tradisi, fitokimia dan sifat farmakologi P. aduncum. Data telah dikumpulkan dari pangkalan data elektronik dari tahun 1978 hingga 2019. Tumbuhan ini secara tradisinya digunakan untuk merawat cirit-birit di Peru serta menyembuhkan luka di Brazil dan Papua New Guinea. Fenol, monoterpena, sesquiterpena serta kromena telah dijumpai dalam tumbuhan P. aduncum, dan sebatian bioaktif ini menyumbang kepada sifatnya sebagai anti-parasit, antimikrob, insektisid, antitumor dan antikanser. Beberapa aktiviti farmakologi P. aduncum telah dilaporkan, terutamanya dalam rawatan penyakit berjangkit dan kanser. Walau bagaimanapun, maklumat mengenai keselamatan dan keberkesanannya pada manusia adalah kurang. Kajian lanjut diperlukan untuk mengkaji manfaat P. aduncum dan potensi pengaplikasiannya dalam persekitaran klinikal.